Interannual variability of the surface temperature of Titicaca lakeusing MODIS winter images (2001-2014) - Váquez Porras, Cėsar Antonio (2022)
The interannual variability of lake surface water temperature (LSWT) was investigated using MODIS images for winter 2001-2014 at Lake Titicaca 15°45'00''S - 69°25'00''O. We use the MOD11A2 Earth Surface Temperature (LST) product, which we will rename as LSWT. Remote sensing LST data was obtained from the MODIS sensor onboard the Terra satellite as an 8-day composite, with a spatial resolution of 1 km. During the austral winter (June, July, and August), the product MOD06L2 cloud fraction showed the clear sky over Lake Titicaca in winter. The LSWT distribution was analyzed by means of images, time series and the coefficient of variation (Cv). Two regions of Titicaca were considered, Lake Mayor (LM) and Lake Menor (Lm). It was discovered that the coefficient of variation of LSWT for the main basin (LM) during the study period did not show significant changes (Cv < 9%). The average value of the surface temperature of the main basin (LM) found in this investigation is approximately 13,224 °C and that of the minor lake (Lm) is equal to 12,695 °C. Finally, using the principal components analysis, a positive trend is observed from 2004 to 2010, the year of the maximum of PC1 for Lago Mayor and Lago Menor.